Spherical activated carbons derived from resin-microspheres for the adsorption of acetic acid. Issue 2 (April 2023) - Wu, Huiling; Wei, Huangzhao; Yang, Xu; Jin, Chengyu; Sun, Wenjing; Deng, Kai; Rong, Xin; Bin, Gu; Sun, Chenglin
Abstract: Separation of small-molecule carboxylic acids, especially acetic acid, from wastewater is challenging due to its high-water solubility, acidity, and low concentration. In this work, resin-derived spherical activated carbon (RSAC) was directly prepared from resin spheres through facile pre-oxidation and carbonization processes. RSAC was characterized by SEM, N2 physisorption, XRD, Raman, element analysis and XPS. RSAC showed high removal rates (> 95.8 %) for a variety of small-molecule carboxylic acids. The initial adsorption capacity of acetic acid over RSAC was 23.4 mg/g and 94 % of the removal rate was retained after five successive adsorption-desorption cycles for 1000 mg/L acetic acid. In addition, RSAC showed a high total organic carbon removal rate (> 80 %) for the high-salinity effluent of catalytic wet air oxidation (CWAO) process. The adsorption of acetic acid over RSAC complied with the pseudo-second-order model and Langmuir model ideally, through Vander Waals force and pore-filling effect. Furtherly, discarded resin microspheres were used to prepare spherical active carbon, which showed 88.2 % removal of acetic acid (1000 mg/L). The benign scheme of "treating wastes by wastes" from economical and environmental aspects was realized. Graphical Abstract: ga1 Highlights: Spherical activated carbon (RSAC) is facilely prepared from resin microspheres. The RSAC shows excellent acetic acid adsorption performance from wastewater. Van der Waals forces and pore-filling effect dominate the adsorption process. Concept of treating wastes (acetic acid) by wastes (discarded resins) is realized.